Internal friction in zirconium-hydrogen alloys at low temperatures - Povolo, Francisco; Bisogni, Eduardo Angel (North Holland Publishing, 1969)
Fil: Povolo, Francisco Comisión Nacional de Energía Atómica; Argentina